(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Rickets is a disorder of mineralization of the growing bone, occurring primarily in infants and young children. It is characterized mainly by impaired bone growth and skeletal deformities. The etiology of rickets is most frequently linked with vitamin D deficiency, although it may also be associated with inadequate nutrition, genetic factors, and certain medical conditions that affect the absorption and metabolism of vital nutrients. The early recognition and timely treatment of rickets are fundamental to preventing permanent disability and promoting optimal physical development in children. This paper explores the essential aspects of early diagnosis and treatment of rickets, focusing on etiology, clinical manifestations, diagnostic strategies, therapeutic principles, and future perspectives.